The Impact of Knowledge Interpretation and Organizational Context on the Use of Electronic Recordkeeping Systems - Lewellen, Matthew; Hooper, Val; Oliver, Gillian (ACIS, 2014)
Transparency and accountability in society is underpinned by the requirement to create and maintain trustworthy digital records. The need (often mandated by legislation) to manage these records has been the primary motivator for the implementation of enterprise-wide Electronic Document and Records Management Systems (EDRMS). However, EDRMS implementations have proved challenging in terms of end-user acceptance of the technology. Drawing on Structuration Theory, the Records Continuum Model and the Technology Acceptance Model, this research explored the factors that influence a user’s intention to contribute documents to an EDRMS. The findings of a quantitative survey undertaken in the context of the New Zealand public sector and the subsequent structural equation modeling revealed a unique set of factors influencing use, including one not previously identified, namely the perceived value of records.